Association of laboratory parameters with chest CT findings in COVID-19 patients - Gurung, Ayeshna; Baral, Reetu; Koirala, Binit; Shrestha, Suman Kumar (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To analyze the Chest CT Scan and association of the severity score with the serum biomarkers D- dimer, C-reactive protein (CRP), Lactate dehydrogenase (LDH) and Ferritin levels. Methods: This is a retrospective study done from the database of Department of Radiology and Department of Pathology at Nobel medical college and teaching hospital during the peak of the second wave of the pandemic from 1st April 2021 to 31 st May 2021. Data for the Chest CT scan and lab parameters were analyzed and correlated. Ethical approval was obtained from the Institutional review committee of Nobel Medical College and Teaching Hospital. Descriptive statistical analysis was performed. Results: A total of 263 cases of Chest CT scan were done in 2 months period who were diagnosed as cases of COVID 19. In this study the severity and scores were taken from the database in the Radiology department. The lab parameters like D-dimer, CRP, LDH and Ferritin levels were studied from the database in the lab. Age of the patients ranged from 19 to 89 years with maximum cases 68 (25.8%) seen in the age group of 50-59 years. According to the chest CT Scan the severity score was in between 11-15 in 92 (48.3%) cases. Fifty six cases showed abnormal levels of D-dimer, Ferritin, CRP and LDH. D-dimer was raised in 26 (46.4%), LDH was raised in 48 (87.2%) while Ferritin and CRP was also raised in all 56 cases. Conclusions: There was a positive correlation between the biomarkers and the Chest CT severity score. The severity of the disease with involvement of the lungs can be estimated by correlating with the lab parameters.